Uncovering the real social, ecological, and environmental benefits of floating photovoltaics in China through refined irradiance-to-power conversion modeling - Liu, Yanbing; Yang, Guoming; Jiang, C. Q. (International journal of green energy, 2025)
Floating photovoltaics (FPV) play a crucial role in achieving energy transition and climate goals, particularly in regions with limited land resources, as they do not occupy land like traditional photovoltaics. Accurately estimating the power generation potential of FPV and its ecological, environmental, and social benefits is challenging. Many existing studies rely on simplistic models that fail to capture the complexities of FPV performance. This study develops a refined resource assessment framework for FPV using multi-source data. The findings indicate that: (1) the annual resource capacity of FPV in China is estimated at 1187.95 TWh, lower than the 1270.03 TWh estimated by conventional models, which overlook various loss mechanisms; (2) the refined model suggests FPV can reduce carbon emissions by 876.95 million tons annually, accounting for 8.86% of China's total emissions, and reduce SO2 and NO X emissions by 237,589.82 tons and 225,710.33 tons annually, respectively; (3) FPV installation could save 48.30 billion m 3 of water annually, representing 0.83% of China's total water consumption; (4) this refined assessment framework enhances the cost-competitiveness of FPV and can stimulate China's renewable energy sector and job creation. Overall, while this study offers vital insights for FPV development in China, it also lays the groundwork for similar research in other countries.